Responses of midgut amylases of Helicoverpa armigera to feeding on various host plants - Kotkar, Hemlata M.; Sarate, Priya J.; Tamhane, Vaijayanti A.; Gupta, Vidya S.; Giri, Ashok P. (Journal of Insect Physiology, 2009)
Midgut digestive amylases and proteinases of Helicoverpa armigera, a polyphagous and devastating insect pest of economic importance have been studied. We also identified the potential of a sorghum amylase inhibitor against H. armigera midgut amylase. Amylase activities were detected in all the larval instars, pupae, moths and eggs; early instars had lower amylase levels which steadily increased up to the sixth larval instar. Qualitative and quantitative differences in midgut amylases of H. amigera upon feeding on natural and artificial diets were evident. Natural diets were categorized as one or more members of legumes, vegetables, flowers and cereals belonging to different plant families. Amylase activity and isoform patterns varied depending on host plant and/or artificial diet. Artificial diet-fed H. armigera larvae had comparatively high amylase activity and several unique amylase isoforms. Correlation of amylase and proteinase activities of H. armigera with the protein and carbohydrate content of various diets suggested that H. armigera regulates the levels of these digestive enzymes in response to macromolecular composition of the diet. These adjustments in the digestive enzymes of H. armigera may be to obtain better nourishment from the diet and avoid toxicity due to nutritional imbalance. H. armigera, a generalist feeder experiences a great degree of nutritional heterogeneity in its diet. An investigation of the differences in enzyme levels in response to macronutrient balance and imbalance highlight their importance in insect nutrition. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: Amylase inhibitors; Diet; Helicoverpa armigera larvae; Midgut amylase; Proteinases

Amylase gene expression patterns in Helicoverpa armigera upon feeding on a range of host plants - Kotkar, Hemlata M.; Bhide, Amey J.; Gupta, Vidya S.; Giri, Ashok P. (Gene, 2012)
Expression of two amylase genes (HaAmy1 and HaAmy2) was studied in Helicoverpa armigera (Hubner; Lepidoptera: Noctuidae) feeding on different host plants and during larval development. Alignment of HaAmy1 and HaAmy2 with other insect amylases shows similarities with known Lepidopteran amylase transcripts. H. armigera amylase gene expression is influenced by the availability of reducing sugars, sucrose and starch content of host plants and further correlates to the pool of reducing sugars in the gut and haemolymph of larvae. HaAmy1 and HaAmy2 during larval development on two host plants viz., maize (cereal) and marigold (ornamental) showed their relative difference. Results support the view that when host plants differ in their macronutrients, relationships of enzymes and substrates are flexible. The present work highlights the distribution of HaAmy1 and HaAmy2 (i) during various stages of insect development (second, fourth and sixth instar, pupa, adult and egg), (ii) in various tissues viz., head, haemolymph, fat body, integument and whole larval body of H. armigera feeding on artificial diet and (iii) in three gut regions of larvae fed on various diets. Complexity in expression of amylase genes suggests existence of mechanisms involved to detect nutrient balance required for avoiding fitness costs and focus their importance in insect nutrition. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Diets; Digestive amylase; Gene expression; Helicoverpa armigera; Nutrition

Functional diversity of the lepidopteran ATP-binding cassette transporters - Barve, Pranoti R.; Tellis, Meenakshi B.; Barvkar, Vitthal T.; Joshi, Rakesh S.; Giri, Ashok P.; Kotkar, Hemlata M. (Journal of Molecular Evolution, 2022)
The ATP-binding cassette (ABC) transporter gene family is ubiquitous in the living world. ABC proteins bind and hydrolyze ATP to transport a myriad of molecules across various lipid-containing membrane systems. They have been studied well in plants for transport of a variety of compounds and particularly, in vertebrates due to their direct involvement in resistance mechanisms against several toxic molecules/metabolites. ABC transporters in insects are found within large multigene families involved in the efflux of chemical insecticides and toxic/undesired metabolites originating from food and endogenous metabolism. This review deals with ABC transporter subfamilies of few agronomically important Lepidopteran pests. The transcriptional dynamics and regulation of ABC transporters during insect development emphasizes their functional diversity against insecticides, Cry toxins, and plant specialized metabolites. To generate insights about molecular function and physiological roles of ABCs, functional and structural characterization is necessary. Also, expansion and divergence of ABC transporter gene subfamilies in Lepidopteran insects needs more systematic investigation. We anticipate that newer methods of insect control in agriculture can benefit from an understanding of ABC transporter interactions with a vast range of natural specialized molecules and synthetic compounds.
Keywords: ABC transporters; Bt; insecticide resistance; Lepidoptera; Plant metabolites

Regulation of trehalose metabolism in insects: from genes to the metabolite window - Tellis, Meenakshi B.; Kotkar, Hemlata M.; Joshi, Rakesh S. (Glycobiology, 2023)
Trehalose is a major circulatory sugar in the haemolymph of insects. It provides instant energy and protection against stress. Trehalose metabolism is associated with insect growth and development. The architecture and spatio-temporal expression dynamics of trehalose metabolism and transport genes are key for regulation. These genes are controlled by various transcription factors, largely linked to nutrition, insect development, and metamorphosis. Also, trehalose levels are affected by substrate affinities and modifications of enzymes involved in the pathway. A feedback mechanism involving the precursors and products can regulate trehalose metabolism. Further, the neuroendocrine system controls trehalose levels under normal and stressed conditions by producing different hormones. Hypotrehalosemic hormones work under surplus energy conditions to activate haemolymph trehalose uptake and degradation. In contrast, hypertrehalosemic hormones stimulate trehalose production in the fat body and its transport to the haemolymph. However, trehalose metabolism regulation in insects needs to be studied in detail. This review discusses aspects of trehalose synthesis, transport, and degradation dynamics in developmental transition and stress response. Unraveling the epigenetic factors, transcriptional control and chemical or genetic modulators can provide further insights into the intricate regulation of trehalose in a development- and tissue-specific manner. This molecular information about effectors and regulators of trehalose metabolism can be applied in developing diverse biotechnological applications.
Keywords: Hormone; Insect development; Metabolic regulation; Stress; trehalose

Trehalose transporter-like gene diversity and dynamics enhances stress response and recovery in Helicoverpa armigera - Tellis, Meenakshi B.; Chaudhari, Bhagyashri Y.; Deshpande, Shweta V.; Nikam, Sanika V.; Barvkar, Vitthal T.; Kotkar, Hemlata M.; Joshi, Rakesh S. (Gene, 2023)
Trehalose is a primary sugar and its distribution across the insect body, regulated by trehalose transporters (TRETs), is essential for sugar metabolism and energy homeostasis. The large diversity of Tret-like sugar trans-porters (ST), belonging to SLC2A transporter family, in polyphagous insects probably contributes to their extremely adaptive nature. We aim to study spatio-temporal expression dynamics and functional relevance of ST transcript variants in the lepidopteran model organism, Helicoverpa armigera. Identification of 69 putative Tret-like HaST transcript variants from databases and their digital gene expression analysis indicated tissue and development-specific expression patterns. Phylogenetic and sequence similarity network analysis of HaSTs signify evolutionary divergence, while motif and structure analysis depicted conserved signatures. In vitro gene expression validation for selected genes depicts that HaST09 and 69 are fat body and haemolymph-specific. While, HaST06, 30, 36 and 57 are developmental stage or sex-specific. HaST69 has high expression in the haemolymph of fifth instar larvae. In the presence of trehalose metabolism inhibitors and abiotic stress, HaSTs expression show dysregulation, indicating their possible association with trehalose metabolism and stress re-covery. In vivo gene silencing of HaST69 resulted in reduced trehalose accumulation in the insect body, sug-gesting its plausible role in sugar metabolism. The overall understanding of HaST diversity and expression dynamics highlights their putative roles in sugar transport during adaptation and stress recovery of insects.
Keywords: Gene expression; Helicoverpa armigera; Stress; Transporter-like; trehalose

Inhibition of trehalose synthesis in lepidoptera reduces larval fitness - Tellis, Meenakshi B.; Mohite, Sharada D.; Nair, Vineetkumar S.; Chaudhari, Bhagyashri Y.; Ahmed, Shadab; Kotkar, Hemlata M.; Joshi, Rakesh S. (Advanced Biology, 2024)
Trehalose is synthesized in insects through the trehalose 6-phosphate synthase and phosphatase (TPS/TPP) pathway. TPP dephosphorylates trehalose 6-phosphate to release trehalose. Trehalose is involved in metamorphosis, but its relation with body weight, size, and developmental timing is unexplored. The expression and activity of TPS/TPP fluctuate depending on trehalose demand. Thus, TPS/TPP inhibition can highlight the significance of trehalose in insect physiology. TPS/TPP transcript levels are elevated in the pre-pupal and pupal stages in Helicoverpa armigera. The inhibition of recombinantly expressed TPP by N-(phenylthio)phthalimide (NPP), is validated by in vitro assays. In vivo inhibition of trehalose synthesis reduces larval weight and size, hampers metamorphosis, and reduces its overall fitness. Insufficient trehalose leads to a shift in glucose flux, reduced energy, and dysregulated fatty acid oxidation. Metabolomics reaffirms the depletion of trehalose, glucose, glucose 6-phosphate, and suppressed tricarboxylic acid cycle. Reduced trehalose hampers the energy level affecting larval vitality. Through trehalose synthesis inhibition, the importance of trehalose in insect physiology and development is investigated. Also, in two other lepidopterans, TPP inhibition impedes physiology and survival. NPP is also found to be effective as an insecticidal formulation. Overall, trehalose levels affect the larval size, weight, and metabolic homeostasis for larval-pupal transition in lepidoptera. Inhibition of trehalose synthesis enzyme TPS/TPP is a good model to study the contribution of trehalose in attaining body weight and in larval-pupal transition. Transcriptomics and metabolomics studies reveal overall reduced energy and dysregulated glucose, protein, and fatty acid metabolism.image
Keywords: Lepidoptera; metabolic homeostasis; trehalose; trehalose 6-phosphate phosphatase

High levels of sinigrin trigger synthesis of fatty acids in Plutella xylostella (L.) - Barve, Pranoti R.; Barvkar, Vitthal T.; Giri, Ashok P.; Kotkar, Hemlata M. (Comparative Biochemistry and Physiology D-Genomics & Proteomics, 2025)
Diamondback moth (Lepidoptera: Plutellidae; Plutella xylostella L.) is a specialist insect of the Brassicaceae family, damaging economically important crops, such as cabbage and cauliflower. Glucosinolates, also known as `mustard oil bombs' are present in all Brassicaceae members, of which sinigrin (allyl-glucosinolate or 2-propenylglucosinolate) is a major aliphatic compound. During herbivory, glucosinolates are converted to toxic isothiocyanates that deter insect pests. P. xylostella possesses glucosinolate sulfatases that desulfate them. Such a conversion renders them unfit for degradation to toxic products. Changes in the larval performance prompted us for RNA sequencing to understand probable adaptation mechanism under sinigrin stress. Differentially expressed genes were found to be related to larval cuticle proteins. Further, gene ontology and KEGG (Kyoto Encyclopedia of Genes and Genomes) analyses depict genes belonging to the categories, integral component of membrane, cellular processes and those involved in biosynthesis of fatty acids. Upregulation of cuticular genes viz. larval cuticle protein-17 (LCP-17), cuticular protein-19 (2CP-19) and ATP binding cassette transporter C7 (ABCC7), ABCC16 was validated by qRT-PCR. Liquid chromatography quadrupole time of flight mass spectrometry analysis of whole larvae feeding on sinigrin and their separated cuticle, depicted abundance of fatty acids. Changes in the topography of the larval cuticle were evident by scanning electron microscopy. Expression of PxABCH1 was corroborated to its role in the transport of cuticular lipids. Notably, molecular docking of PxABCH1 with cuticular fatty acids showed favorable binding interactions. To summarize, integrated transcriptomic and metabolomic analyses suggest that in response to a diet containing a high dose of sinigrin, P. xylostella re-programs metabolic pathways related to fatty acid biosynthesis that directly influence insect development.
Keywords: ABC transporter; Cuticle; Host metabolite; Metabolome; Plutella xylostella; Sinigrin; Transcriptome